World Environmental and Water Resources Congress 2017 2017
DOI: 10.1061/9780784480595.011
|View full text |Cite
|
Sign up to set email alerts
|

Precision Counting of Sandhill Cranes in Staten Island by FAA Approved Small Unmanned Aerial System Night Missions

Abstract: One important challenge for Sandhill Crane conservation is the collection of regular, accurate counts of birds roosting in flooded areas at night. Estimates of roost site numbers are an important way to track population size over time and detect any changes in site selection that may be a function of management or changes in site conditions. Traditional methods for estimating roosting crane numbers are morning and evening counts of cranes as they arrive at or depart their roosting sites. The accuracy of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Guidelines for using drones to study animals usually suggest that small drone sizes (<2 kg), implementing further take‐off distances from the subject/s, higher flight heights, slow speeds and horizontal rather than vertical approaches can reduce the disturbance imposed on birds, but these responses can vary between species (Barr et al., 2020 ; Duporge et al., 2021 ; Lyons et al., 2018 ; Marchowski, 2021 ; Sorrell et al., 2023 ; Vas et al., 2015 ; Weimerskirch et al., 2018 ; Wilson et al., 2021 ). Drone use in crane research and monitoring is in its infancy, with studies generally using drones to estimate population densities (e.g., Sandhill Cranes Grus canadensis (Stark et al., 2017 ), Siberian Cranes Leucogeranus leucogeranus (Wen et al., 2021 ) and Common Cranes ( Grus grus ) (Chen et al., 2023 )). Exploratory work investigating 33 bird species has shown that drones generally impart minimal disturbance when counting populations; however, the responses of Common Cranes towards drones in this study were inconclusive (Marchowski, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines for using drones to study animals usually suggest that small drone sizes (<2 kg), implementing further take‐off distances from the subject/s, higher flight heights, slow speeds and horizontal rather than vertical approaches can reduce the disturbance imposed on birds, but these responses can vary between species (Barr et al., 2020 ; Duporge et al., 2021 ; Lyons et al., 2018 ; Marchowski, 2021 ; Sorrell et al., 2023 ; Vas et al., 2015 ; Weimerskirch et al., 2018 ; Wilson et al., 2021 ). Drone use in crane research and monitoring is in its infancy, with studies generally using drones to estimate population densities (e.g., Sandhill Cranes Grus canadensis (Stark et al., 2017 ), Siberian Cranes Leucogeranus leucogeranus (Wen et al., 2021 ) and Common Cranes ( Grus grus ) (Chen et al., 2023 )). Exploratory work investigating 33 bird species has shown that drones generally impart minimal disturbance when counting populations; however, the responses of Common Cranes towards drones in this study were inconclusive (Marchowski, 2021 ).…”
Section: Introductionmentioning
confidence: 99%